(untitled) (Global Journal of Science Frontier Research, 2019)
A study was conducted to assess the genetic diversity of locally collected cucumber germplasm by using morphological markers at the Plant Genetic Resources Centre of the Bangladesh Agricultural Research Institute, Gazipur, Bangladesh during March to August 2017. Quantification of variability for each character was done by using Shannon Weaver Diversity Index (SWDI). Characterization data were further subjected to Principal Component Analysis (PCA). The collection exhibited medium to high variations for both the qualitative and quantitative characters as reflected by mean diversity indices 0.62 and 0.63 respectively. Two phonological characters viz. days to harvest and days to pistilate flower respectively showed the weakest indices 0.26 and 0.32. First four principal components accounted for 80% of the observed variations. Analysis of the factor loading of component characters showed that fruit characters to be the major attributes of variation. Cluster analysis performed on the germplasm gave 3 distinct clusters. Genotypes AMA-406and Ac-207 in cluster I found to be potential for breeding purpose.